Formulation Development, Evaluation, and Optimization of Mucoadhesive Patches of Venlafaxine Hydrochloride for Buccal Delivery - Nilima Thombre; Ashwini Dokhale (International Journal of Pharma and Bio Sciences, 2021)
The present experimental study aimed to design, develop, evaluate and optimize the buccal patch formulations of Venlafaxine hydrochloride using hydrophilic and hydrophobic polymers, having different concentrations. Venlafaxine hydrochloride is an antidepressant with a high first-pass metabolism and a low oral bioavailability of 40%. To increase the bioavailability and to reduce the dosing frequency of the drug, an attempt was made by formulating mucoadhesive patches of Venlafaxine Hydrochloride for buccal delivery. An Optimized buccal patch formulation was prepared by the solvent casting method. Eudragit RS-100 polymer was used as film forming polymer while HPMC E-15 was incorporated to provide the patches with bioadhesive properties and to modify the rate of drug release. A 32 full factorial design was employed to design batches of the formulation. The concentration of Eudragit RS 100 and HPMC E15 was selected as two independent variables while cumulative percent drug release was a dependent variable. Prepared batches of formulation were evaluated for content uniformity, thickness, weight variation, swelling index, surface pH, tensile strength, elongation at break, mucoadhesive strength, mucoadhesion time, in vitro drug release, etc. The optimized batch of the buccal patch has a drug release of 95.29 ± 0.42 %, an ex–vivo residence period of 3782.51 minutes, and a content uniformity of 97.96 0.17 percent to 103.24 0.48 percent. The ex–vivo residence time ranged from 378 ± 2.51 min to 470 ± 2.08 min. Mucoadhesive strength and swelling index were directly proportional to the concentration of hydrophilic polymer. The study suggested that the buccal patch significantly enhanced the bioavailability of Venlafaxine hydrochloride and modified the drug release.